DESAIN DAN IMPLEMENTASI PEMBELAJARAN COLLABORATIVE TIPE SEND-A-PROBLEM PADA PEMBELAJARAN MATEMATIKA - Syahrial Syahrial (Universitas Batanghari Jambi, 2018)
Abstract: The purpose of this research was to know effect of the type of collaborative learning send-a-problem the resuldt of learning mathematics student. The kind of this research was pre-experiment and the design of this research used randomized control group only design. The population of this research was all of students grade XI MIA SMAN 1 Padang Sago academic year of 2017/2018. The sample was class XI MIA2 as experimental and XI MIA1 as control class. The result that analyzed in this research the result of cognitif learning and affective learning. The technique of analyze data that used to hypothesis testing was the analyse of similarity analysis of two on average by using the t-test because normal data distribution and data group that have a homogen variance on cognitif learning and the analyse of similarity analysis of the two parties by using the z-test on affective learning. Based on the analysis of the data, it can said that the students who taught by guided discovery with concret method and had mean score greater (77,94) then student who were tough by convensional method (71,17). After test done so, it get calculate tcalc = 3,33 and ttable = 1,689 (tcalc > ttable) at significance level of 0,05 with confidence level 95%. Based on calculation show that tcalculate > ttabel means H0 rejected and H1 accepted, so it can be concluted that the type of collaborative learning send-a-problem the resuldt of learning mathematics student.Keywords: Colaboratif, Send-a-problem